The rural voter the politics of place and the disuniting of America - Jacobs, Nicholas F.; Shea, Daniel M. 1961- (Columbia University Press, 2024)
"The divide between rural and urban America is vast and growing. Electoral maps separating deep reds from vivid blues expose not only political rifts, but a nation on the cusp of disunion. While others have touched on elements of this historical change, this book offers the most comprehensive, systematic exploration of the rise and consequences of the "rural voter." Through a mix of historical research, contemporary narratives, and the largest survey of rural Americans ever conducted, political scientists Nick Jacobs and Daniel M. Shea explore the roots of this unprecedented change and lay bare the dangers of rural America's steadfast alliance with one party. The authors leverage two hundred years' worth of data on voting patterns, census information, and novel historical detail to document the growing chasm between urban and rural voters. Their findings challenge traditional stories of the 1920s, the New Deal, and the Reagan Revolution and explain how the Republican Party has come to dominate rural America in the twenty-first century. Moving beyond case-study approaches, common in many recent works, Rage and Rebellion explores the attitudes and opinions of voters themselves: a set of three national surveys boasting 10,000 rural respondents and five thousand non-rural Americans. The book argues that rural Americans today are not inherently conservative. Instead, their vote is the consequence of a distinct cultural resentment. Rural voters believe they are the last guardians of a uniquely American way of life, a culture rooted in hard work, family, love of country, and place. In the end, this book offers a cautionary tale to pundits and politicians who believe they can paper over differences with better policies, sharper talking points, or more stops in the flyover country"--
Keywords: Conservatism / United States; Right and left (Political science) / United States; Rural-urban relations / Political aspects / United States; Rural population / United States / Attitudes; Republican Party (U.S. : 1854- ); Political culture / United States; Conservatisme / États-Unis; Relations villes-campagnes / Aspect politique / États-Unis; Conservatism; Political culture; Right and left (Political science); Rural population / Attitudes; United States